Hubungan Intimal Media Thickness Karotis Dengan Faktor Risiko Kardiovaskular pada Pasien Gagal Ginjal Kronik Pra-Dialisis - Vicky Wahidji; Ismoyo Sunu; Dede Kusmana (The Indonesian Heart Association, 2009)
Background. The incidence of cardiovascular diseases is markedly higher in patients with Chronic Kidney Disease (CKD). Both conventional and non-conventional cardiovascular risk factors play a role in this observed phenomenon. In general population, Intima Media Thickness (IMT) has been found to correlate with the incidence of cardiovascular disease and it also serves as an independent predictor of cardiovascular mortality in CKD patients undergoing chronic hemodialysis.Objectives. To investigate the relationship between carotid IMT with cardiovascular risk factors in a population of CKD patients prior to chronic hemodyalisis.Methods. This was a cross sectional study to measure carotid IMT in CKD patients using B-mode ultrasonography. Glomerular Filtration Rate of subjects was calculated by Modification of Diet in Renal Disease (MDRD) formula. The cardiovascular risk factors assessed included plasma blood sugar, lipid profile, renal function, blood pressure, body weight, sex and age.Results. We recruited 76 subjects, mostly male, over 65 years of age and also obese (mean body mass index of 26,3 kg/m2). Most of the subjects had uncontrolled systolic blood pressure, plasma sugar level and lipid profile. The mean systolic blood pressure was 134.21 mmHg, fasting blood sugar 110mg/dl, high and low density lipoprotein were 41.83 mg/dl and LDL 117.36 mg/dl, respectively. There was also a trend of CKD resulted in mean of IMT with the fall in GFR; stadium 3, 4 and 5 of CKD resulted in mean IMT of 0.9 and 1.3 mm, respectively.Conclusion. We did not find any correlation between IMT and sex, age, hypertension, diabetes mellitus, smoking nor obesity. The decline in renal function was associated with a significant increase in IMT (p < 0.005).